Contributos à análise do amor entre casais que vivem na rua - Moreira, Nádia Xavier; Figueiredo, Ana Cláudia Silva (Argumentum, 2023)
This article aims to address the loving relationships - affective and sexual ones - among the homeless, understanding such relations as an event - culturally significant instances in a given context. The present study is grounded on the theoretical constructions of Marshall Sahlins about this category, as well as on the studies focused on the analysis of how bonds and emotions are combined and inscribed in the social field. From participant observation and analysis of bibliographic productions, we sought to understand how these loving relationships are experienced. The results of the study indicate that love on (of) the street is an event as the street is reinvented. Before being a place of suffering, it is a space for the private, for experiencing intimacy, for building bonds and loving relationships. In their daily lives, homeless people go through this experience according to their way of life, within their field of possibilities, in general, these encounters are inscribed as stories of possible loves.